Drying-Induced Hornification in Cellulose Nanofiber–PLA Composites Improving Mechanical and Thermal Stability - Sholahuddin Sholahuddin; Eka Fitriastuti; Dian Yosi Arinawati (Green Engineering Society, 2026)
Steam explosion pretreatment is widely used to facilitate the production of cellulose nanofibers (CNFs) from lignocellulosic biomass; however, the influence of pretreatment severity on the performance of CNF-reinforced polylactic acid (PLA) composites remains insufficiently understood. This study investigated the effect of steam explosion pressures of 35 and 40 atm on the mechanical, thermal, and morphological properties of CNF/PLA composites prepared from oil palm empty fruit bunches (EFB). CNFs were produced by steam explosion followed by mechanical fibrillation and incorporated into a PLA matrix at a 1:1 dry weight ratio. The composite prepared using 35 atm exhibited superior mechanical performance, with a tensile strength of 9.22 ± 0.01 MPa and a Young's modulus of 2.26 ± 0.12 GPa. Increasing the pretreatment pressure to 40 atm slightly delayed the onset of thermal degradation and reduced the cold crystallization temperature, suggesting enhanced heterogeneous nucleation during heating. However, the higher pressure also reduced tensile properties and significantly decreased the residual char content, indicating more extensive removal of lignin and possible hornification and partial cellulose depolymerization. These results demonstrate a trade-off between mechanical reinforcement and thermal performance as pretreatment severity increases. Overall, a steam explosion pressure of 35 atm provided the most balanced combination of mechanical and thermal properties, offering useful guidance for optimizing CNF-reinforced PLA biocomposites derived from oil palm biomass.